Rapid removal of ammonium from domestic wastewater using polymer hydrogels - Cruz, Heidy (2018)
To date, technologies to recover ammonium from domestic wastewater from the mainstream have not found widespread application. This is largely due to the low ammonium concentrations in these wastewater streams. This paper reports on the use of polymer hydrogels for rapid sorption of ammonium from domestic wastewater coupled with efficient regeneration by mild acid washing. The sorption capacity of the hydrogel was 8.8–32.2 mg NH4–N/g, which corresponds to removal efficiencies ranging from 68% to 80% NH4–N, increasing proportionally with the initial ammonium concentration. It was, however, unaffected by changes in pH, as the sorption capacity remained constant from pH 5.0–8.0. Importantly, effective regeneration of the hydrogels under mildly acidic conditions (i.e. pH 4.0) was demonstrated with minimal loss in sorption performance following multiple sorption/desorption cycles. Overall, this study highlights the potential of low-cost polymer hydrogels for achieving mainstream ammonium recovery from domestic wastewater.